ANALISIS KESULITAN BELAJAR SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA MATERI OPERASI HITUNG PECAHAN KELAS V SD NEGERI CEPAGAN 01 BATANG - Meilia Fina Pratiwi; M. Arief Budiman; Fajar Cahyadi (Universitas Negeri Medan, 2020)
Abstract : Analysis of Student Learning Difficulties in Solving Mathematical Problems in Counting Fractions Operations in Class V Elementary School Cepagan 01 Batang. The purpose of this research is to describe students' mistakes in solving mathematical problems, describe learning difficulties in solving mathematical problems, and find out the factors that influence learning difficulties in solving mathematical problems of fifth grade students. This type of research is descriptive qualitative. The results of this study indicate that the highest student error is in seeing (checking) the answers again. While the lowest student error is in understanding the problem. From the results of the percentage of student errors shows that most students still have difficulty in solving story problems, doing math calculations, teacher learning styles that are applied, and the lack of student responses. In addition, student learning difficulties can be influenced by internal and external factors. Keywords : Analysis, Learning Difficulties, Mathematical Problem Solving, Fractional Count Operations. Abstrak : Analisis Kesulitan Belajar Siswa dalam Memecahkan Masalah Matematika Materi Operasi Hitung Pecahan Kelas V SD Negeri Cepagan 01 Batang. Tujuan penelitian untuk mendeskripsikan kesalahan siswa dalam memecahkan masalah matematika, mendeskripsikan kesulitan belajar dalam pemecahan masalah matematika, dan mengetahui faktor yang mempengaruhi kesulitan belajar dalam pemecahan masalah matematika. Jenis penelitian ini adalah deksriptif kualitatif . Hasil penelitian ini menunjukkan bahwa kesalahan siswa paling tertinggi terdapat pada melihat (mengecek) kembali jawaban. Sedangkan kesalahan siswa terendah terdapat pada memahami masalah. Dari hasil persentase kesalahan siswa menunjukkan bahwa sebagian besar siswa masih mengalami kesulitan dalam menyelesaikan soal cerita, melakukan penghitungan matematika, gaya belajar guru yang diterapkan, dan kurangnya respon respon siswa. Selain itu, kesulitan belajar siswa dapat dipengaruhi oleh faktor internal dan faktor eksternal. Kata Kunci : Analisis, Kesulitan Belajar, Pemecahan Masalah Matematika, Operasi Hitung Pecahan.